Application of protection motivation theory and cultural tightness-looseness for predicting individuals' compliance with the government's recommended preventive measures during regular prevention and control of the COVID-19 pandemic in China - Liu, Yi; Jiang, Xiaoyuan (Frontiers in Public Health, 2023)
During regular prevention and control of the COVID-19 pandemic, it remains necessary to abide by the government’s recommendations to further curb the pandemic. However, little is known about individuals’ compliance with the government’s recommended preventive measures during this period. The current study introduces perceived cultural tightness-looseness into protection motivation theory (PMT) to investigate individuals’ compliance with the government’s recommended preventive measures during regular prevention and control of the COVID-19 pandemic in China. We collected a total of 443 valid questionnaires and used Latent Moderated Structural Equations (LMS) to test the research hypotheses. The results indicated that media exposure to COVID-19-related information significantly predicted perceived severity, maladaptive rewards, self-efficacy, response efficacy, and response cost. Perceived severity, self-efficacy, and response efficacy had significant effects on protection motivation, which, in turn, was positively associated with individuals’ compliance with the government’s recommended preventive measures. In addition, implementation intention acted as a mediator, significantly moderated by perceived cultural tightness-looseness, between protection motivation and individuals’ compliance. In conclusion, the current study investigated individuals’ compliance with the government’s recommended preventive measures and explored its influencing factors and mechanisms during regular prevention and control. It helps to better predict and explain individuals’ compliance and contributes to the literature on the regular COVID-19 pandemic prevention and control and on PMT. Besides, it provides some practical guidance to promote individuals to comply with the precautions.